Understanding Health Equity: Key Concepts, Debates, and Developments in Canada - Khan, Attia (Health Tomorrow: Interdisciplinarity and Internationality, 2015)
Health inequalities exist and persist due to the quality and distribution of the social determinants of health, i.e., the day to day circumstances people live in. These circumstances are determined by governing policies and practices which are influenced by the State’s political ideology and its socio-economic structures. Using a political economy approach, this paper takes a critical review of the literature on health equity in the Canadian context and clarifies key concepts pertaining to health equity and human rights. Findings of this review show that Canada has been performing poorly in addressing growing health inequalities, in part because of Canada’s increasingly neo-liberal stance on public health over the last decade. This paper will argue that a human rights framework can offer a concrete tool for restructuring public policies and for taking action against these inequalities. By placing health equity on the policy agenda, Canada can help reduce social and income inequalities and optimize the health of its populations.